Clinical Autopsy of a Reverse Osmosis Membrane Module - Gonzalez-Gil, Graciela; Behzad, Ali Reza; Farinha, Andreia S. F.; Zhao, Chengyan; Bucs, Szilard S.; Nada, Tariq; Das, Ratul; Altmann, Thomas; Buijs, Paulus J.; Vrouwenvelder, Johannes S. (Frontiers in Chemical Engineering, 2021)
The desalination of seawater using reverse osmosis membranes is an attractive solution to global freshwater scarcity. However, membrane performance is reduced by (bio)fouling. Membrane autopsies are essential for identifying the type of fouling material, and applying corrective measures to minimize membrane fouling. Information from full-scale membrane autopsies guiding improved plant operations is scant in the formal literature. In this case-study, a reverse osmosis membrane from a full-scale seawater desalination plant with a feed channel pressure drop increase of about 218% was autopsied. The simultaneous determination of microbial cells, ATP, and total organic carbon abundances per membrane area allowed estimating the contributions of biofouling and organic fouling. The abundance of microbial cells determined by flow cytometry (up to 8 × 10^8 cells/cm2), and ATP (~10000 pg/cm2) were rather homogeneously distributed on the membrane. Inorganic fouling was also important, and followed a similar coverage distribution to that of biofouling. Iron (~150 ug/cm2, estimated by ICP-MS) was the main inorganic foulant. High-resolution SEM-EDS imaging of cross-sectioned membranes allowed assessing the thickness of the fouling layer and its elemental composition. Imaging results further supported the results of homogeneous fouling coverage. Moreover, imaging revealed both zones with and without compression of the polysulfone layer, suggesting that the stress due to operating pressure was heterogeneous. The procedure for this membrane autopsy provided a reasonable overview of the diverse contributors of fouling and might be a starting point to building a consensus autopsy protocol. Next, it would be valuable to build a RO membrane database, which can be used as a guidance and diagnostic tool to improve the management and operation of RO desalination plants.